Quantitative MRI-Based Analysis Identifies Developmental Limbic Abnormalities in PCDH19 Encephalopathy. (25th June 2020) - Lenge, Matteo; Marini, Carla; Canale, Edoardo; Napolitano, Antonio; De Masi, Salvatore; Trivisano, Marina; Mei, Davide; Longo, Daniela; Rossi Espagnet, Maria Camilla; Lucenteforte, Ersilia; ,; Barba, Carmen; et al.
Abstract: Protocadherin-19 (PCDH19) is a calcium dependent cell-adhesion molecule involved in neuronal circuit formation with prevalent expression in the limbic structures. PCDH19 -gene mutations cause a developmental encephalopathy with prominent infantile onset focal seizures, variably associated with intellectual disability and autistic features. Diagnostic neuroimaging is usually unrevealing. We used quantitative MRI to investigate the cortex and white matter in a group of 20 PCDH19 -mutated patients. By a statistical comparison between quantitative features in PCDH19 brains and in a group of age and sex matched controls, we found that patients exhibited bilateral reductions of local gyrification index ( l GI) in limbic cortical areas, including the parahippocampal and entorhinal cortex and the fusiform and lingual gyri, and altered diffusivity features in the underlying white matter. In patients with an earlier onset of seizures, worse psychiatric manifestations and cognitive impairment, reductions of l GI and diffusivity abnormalities in the limbic areas were more pronounced. Developmental abnormalities involving the limbic structures likely represent a measurable anatomic counterpart of the reduced contribution of the PCDH19 protein to local cortical folding and white matter organization and are functionally reflected in the phenotypic features involving cognitive and communicative skills as well as local epileptogenesis.